PEMBERIAN ZAKAT PRODUKTIF UNTUK KINERJA MODAL USAH DAN KESEJAHTERAAN EKONOMI MUSTAHIK PADA LEMBAGA AMIL ZAKAT NASIONAL NURUL HAYAT DI BOJONEGORO - Luthfan Hibatul Wafi; Sri Herianingrum (Universitas Airlangga, 2019)
This research aims to find out and analyze the influence of productive zakat to mustahiq’s business performance and economic welfare at National Amil Zakat Institution Nurul Hayat in Bojonegoro. LAZNAS Nurul Hayat Bojonegoro is one of amil zakat institutions that can develop programs in managing the largest zakat in Bojonegoro. Population in this research is all mustahiqs who received zakat from Amil Zakat Institution Nurul Hayat Bojonegoro. Sampling technique used is non-probability sampling by using purposive sampling method. There are 156 mustahik obtained that received productive zakat.The type of data used is primary data, while data collection method is questionnaire.Keywords: productive zakat, mustahiq’sbusiness performance, mustahiq’s economic welfare